Standard Essential Patents and FRAND - Mishra, Amrita (International Journal of Psychosocial Rehabilitation, 2025)
This paper discusses the concept of Standard Essential Patents and Fair, reasonable and non-discriminatory terms on which these patents are expected to be licensed by the owners. The paper discusses the role that the standard setting organizations play in declaring a technology as a Standard essential technology and ensuring that the owner is willing to license it on FRAND terms. The paper also discusses the interplay of competition law and intellectual property law because with regards to SEPs before discussing the Indian position through some of the decisions by the courts. The paper concludes with pondering upon the need for a defined set of laws regarding SEP licensing and a specialised agency to look over the matters relating the same.